SISTEM PEMBELAJARAN DI TK SATU ATAP LIMA PULUH SELAMA MASA PANDEMI - Kholida Munasti; Na'imah Na'imah (PG-PAUD Trunojoyo, 2022)
The epidemic of coronavirus disease 19 (Covid-19) has dominated the world for about two years. This disrupts all human activity, one of which is in the field of education. Learning during a pandemic really worries teachers and parents  about  learning that schools provide students with an online system. Therefore, researchers want to see the online learning process during a pandemic. The purpose of this study was to find a learning system for the TK Satu Atap Lima Puluh in Kabupaten Batu Bara, Sumatera Utara during the Covid-19 pandemic. The method chosen in this study is qualitatively descriptive. Observations and interviews were used to collect data. The respondents to the survey were parents of one teacher and four students. The data analysis technique used is to describe exactly what the researcher receives. The  research phase begins with observations, interviews,  data reductions, and data analysis. The results showed that the learning process still followed the demands of parents and schools, the learning media did not vary much even mostly only used blackboards and markers and the teacher only explained what was written. Researchers recommend that this research  be done on a larger scale so that more meaningful learning can be applied to other educational environments.